CoNiCrMo, FeCrNi, NiCr and FeNiAlMo modified iron based alloy coating deposited by plasma transferred arc process - Yilmaz, S. O.; Teker, T. (Natl Inst Optoelectronics, 2013)
The technique of alloying an X120Mn12 steel substrate with the plasma transferred arc process was used to develop a surface with high toughness and wear resistance in high temperature applications. Co, Cr, Al and Ni-intermetallic phases were formed inside an Fe-based composite surface coating. The phase transformations on these coated surfaces were comprehensively examined using a combination of scanning electron microscopy and energy dispersive spectrometry microanalysis. The microstructure studies of the superficial layers of the coating revealed an inter-dendritic austenite (gamma) phase structure and fine eutectic Ni-based inter-metallics.
Keywords: PTA; X120Mn12; Coating